Cortical processes of speech illusions in the general population. Issue 1 (December 2016) - Schepers, E.; Bodar, L.; Os, J.; Lousberg, R.
Abstract Background There is evidence that experimentally elicited auditory illusions in the general population index risk for psychotic symptoms. As little is known about underlying cortical mechanisms of auditory illusions, an experiment was conducted to analyze processing of auditory illusions in a general population sample. In a follow-up design with two measurement moments (baseline and 6 months), participants (n = 83) underwent the White Noise task under simultaneous recording with a 14-lead EEG. An auditory illusion was defined as hearing any speech in a sound fragment containing white noise. Results A total number of 256 speech illusions (SI) were observed over the two measurements, with a high degree of stability of SI over time. There were 7 main effects of speech illusion on the EEG alpha band—the most significant indicating a decrease in activity at T3 (t = −4.05). Other EEG frequency bands (slow beta, fast beta, gamma, delta, theta) showed no significant associations with SI. Conclusion SIs are characterized by reduced alpha activity in non-clinical populations. Given the association of SIs with psychosis, follow-up research is required to examine the possibility of reduced alpha activity mediating SIs in high risk and symptomatic populations.